2018
DOI: 10.1088/1475-7516/2018/01/048
|View full text |Cite
|
Sign up to set email alerts
|

On the cosmology of scalar-tensor-vector gravity theory

Abstract: Abstract. We consider the cosmological consequences of a special scalar-tensor-vector theory of gravity, known as MOG (for MOdified Gravity), proposed to address the dark matter problem. This theory introduces two scalar fields G(x) and µ(x), and one vector field φ α (x), in addition to the metric tensor. We set the corresponding self-interaction potentials to zero, as in the standard form of MOG. Then using the phase space analysis in the flat Friedmann-Robertson-Walker background, we show that the theory pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…It has been shown that the theory has a true sequence of cosmological epochs. In other words, the cosmos starts from a radiation-dominated universe and then enters a matterdominated phase, before finally evolving towards an accelerated de Sitter universe (Jamali et al 2018). One main issue which should still be addressed by MOG is cosmic structure formation.…”
Section: Mogmentioning
confidence: 99%
“…It has been shown that the theory has a true sequence of cosmological epochs. In other words, the cosmos starts from a radiation-dominated universe and then enters a matterdominated phase, before finally evolving towards an accelerated de Sitter universe (Jamali et al 2018). One main issue which should still be addressed by MOG is cosmic structure formation.…”
Section: Mogmentioning
confidence: 99%
“…One is to pursue a description without dark matter employing only baryonic matter and the baryonic density ρ b . This approach has been explored with some success [25][26][27] but requires further exploration in the future. The second approach is to promote the gravitational VG (spin 1 vector graviton) degree of freedom as a dominant density ρ φ in the early universe, so that it dominates the baryon density ρ b for the time before the reionization phase when stars and galaxies are first formed [2,22].…”
Section: Introductionmentioning
confidence: 99%
“…In the matter dominated phases, the growth of the scale factor is found to be as a(t) ∝ t 0.46 and a(t) ∝ t 0.52 slower than the growth in standard model and the present model reported above as a(t) ∝ t 2/3 . Although, it should be mentioned that as Jamali et al (2018) have reported, the standard MOG possesses a valid sequence of standard cosmological eras.…”
Section: Sequence Of Cosmological Epochsmentioning
confidence: 87%